2006
DOI: 10.1080/13561820500498154
|View full text |Cite
|
Sign up to set email alerts
|

The Interprofessional Rural Program of British Columbia (IRPbc)

Abstract: The Interprofessional Rural Program of British Columbia IRPbc was established in 2003 as an important first step for the Province of British Columbia, Canada, in creating a collaborative interprofessional education initiative that engages numerous communities, health authorities and post-secondary institutions in working toward a common goal. Designed to foster interprofessional education and promote rural recruitment of health professionals, the program places teams of students from a number of health profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 6 publications
0
43
0
Order By: Relevance
“…Reports from successful organizations could have been used to influence administrators, and funding to support implementation over several terms might have led to greater uptake. Timing of funding availability has been reported as important for other programs where potential participants were excluded because of their inability to mobilize in time [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Reports from successful organizations could have been used to influence administrators, and funding to support implementation over several terms might have led to greater uptake. Timing of funding availability has been reported as important for other programs where potential participants were excluded because of their inability to mobilize in time [9].…”
Section: Discussionmentioning
confidence: 99%
“…Scheduling has also been identified as an important issue in IPE, particularly when students are being assigned to rural locations [9]. Most often curriculum developers for different health science programs do not plan clinical placement requirements and sequencing to support IPE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The IRPbc (Interprofessional Rural Program of British Columbia) -a Canadian IPE program -engages pre-licensure learners in clinical placements in rural settings, emphasizing interprofessional learning through weekly projects, meetings, and shadowing [14,15]. The IRPbc study [14,15] reported positive results, but these findings were based solely on qualitative methods.…”
Section: Introductionmentioning
confidence: 96%